Establish in Medellin (Colombia) an in-house library to identify clinically important filamentous fungi by MALDI-TOF MS - Gómez-Velásquez, Juan C. (2018)
[Excerpt] Epidemiology of fungal infections has changed in an important manner in the last decades, however timely diagnosis and treatment are still a current challenge. Accurate and swift identification of the agents that cause fungal infections are paramount, since sources of infection, differences between therapeutic regimes, and in-vitro susceptibility profiles may vary amongst species and strains. The application of Matrix Assisted Laser Desorption/Ionization Time-Of-Flight (MALDI-TOF) mass spectrometry (MS) for the identification of fungal samples is currently wellestablished based on the remarkable reproducibility for the measurement of constantly expressed and highly abundant proteins, such as ribosomal proteins, that are used to generate a fingerprint profile. However, the use of this tool for filamentous fungi identification in routine clinical laboratories is still limited due to several reasons, such as, 1) the biological variations among fungal clinical isolates or 2) the lack of a spectrum of reference in commercial libraries for the identification of emerging, endemic and prevalent fungi in tropical regions. Consequently, the establishment of an in-house library that will contain spectra for prevalent fungi found in routine mycological diagnosis at a local level, and of those not included in commercial libraries, is a demand. The aim of this research was to establish a library of spectra for the identification of clinically important filamentous fungi through MALDI-TOF MS in a mycological diagnosis laboratory. [...]